Global molecular epidemiology of the incomplete CirA protein related to cefiderocol resistance in Klebsiella pneumoniae: a genome-based study - Haiyan Long; Yu Feng; Zhiyong Zong (Microbiology Spectrum)
ABSTRACT CirA is an iron transporter comprising 657 amino acids in Klebsiella pneumoniae, and incomplete CirA alone leads to reduced susceptibility to cefiderocol. We performed a genome-based analysis to study the prevalence of incomplete CirA in K. pneumoniae through analyzing all genomes of this species (n = 55,517, as of 26 October 2023) available in NCBI. We detected incomplete CirA in 633 (1.27%) genomes with the corresponding strains collected since 1911, across 44 countries on six continents, and mostly (n = 563, 88.94%) from humans. Notably, 77 (12.16%) genomes had incomplete CirA in combination with β-lactamases (NDM-1, NDM-5, NDM-7, or KPC-3 plus SHV-11) known to confer cefiderocol resistance. We identified 189 variants of incomplete CirA, including two particularly common ones, a 362-amino-acid remnant due to frameshift by a deletion at cirA nucleotide position 1,083 (116/633, 18.33%) and a 562-amino-acid remnant due to premature stop resulting from a mutation at nucleotide position 1,684 (71/633, 11.22%). The 362-amino-acid remnant was mainly found in ST26 (39/116), ST34 (36/116), and ST359 (31/116) strains. The 562-amino-acid remnant was almost exclusive to ST86 (69/71), particularly related to the hypervirulent capsule type K2. Clonal outbreaks (ST26 in USA, ST34 in UK, and ST86 in Vietnam) and cross-border transmission (ST34 in UK and Portugal) were observed. However, this study has limitations, as the analyzed publicly available K. pneumoniae assemblies are biased, and only mutations resulting in incomplete CirA were considered. In conclusion, K. pneumoniae with incomplete CirA is a global concern, highlighting the urgent need for heightened vigilance and further studies.IMPORTANCECefiderocol is a critically important antimicrobial agent against multidrug-resistant organisms including carbapenem-resistant Klebsiella pneumoniae. We performed a genome-mining study and found incomplete CirA (an iron transporter), which is related to cefiderocol resistance, in a small proportion (1.27%) of publicly available K. pneumoniae genomes. However, K. pneumoniae strains with incomplete CirA are globally distributed and have been present for over a century, well before the clinical use of cefiderocol. One hundred eighty-nine incomplete CirA variants were identified, suggesting multifactorial causes. Almost all publicly available genomes of ST26, ST34, and ST86 K. pneumoniae strains with incomplete CirA have a wide geographic distribution, pointing to the potential existence of particular lineages prone to develop resistance to cefiderocol. Clonal outbreaks and cross-border transmission of strains with incomplete CirA were detected. Incomplete CirA was associated with the hypervirulent K2-ST86 lineage or high-risk multidrug resistance ST16 clone, posing an increased threat or challenge to treatment and infection control.